Provision of Janitorial services [Tender documents : T31383960] (MENA Report, 2016)
Notes: Questions & request for clarifications due no later than April 15, 2016 @ 2:00 PM. Proposers are invited to attend a Pre-Proposal meeting at the District~s Headquarters (43885 South Grimmer Boulevard, Fremont, CA 94538) on April 12, 2016 at 10:00 a.m. Attendance is not mandatory, but strongly recommended.